A high entropy carbon-based light-responsive nanoparticle and its preparation method and application

By introducing high-entropy ceramic structures and single crystal preparation methods into carbon-based photoresponsive materials, the problems of low photothermal conversion efficiency and unstable crystal structure of traditional carbon-based photoresponsive materials are solved, and high-efficiency photothermal conversion and excellent mechanical properties are achieved.

CN117586012BActive Publication Date: 2025-04-18BOSIDENG DOWN WEAR LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311072656.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-04-18
Estimated Expiration
2043-08-24

AI Technical Summary

Technical Problem

Traditional carbon-based photoresponsive materials have problems of low photothermal conversion efficiency and unstable crystal structure.

Method used

By forming a zirconium carbide-based high-entropy ceramic based on a narrow band gap zirconium carbide material, and combining the preparation method of single crystal high-entropy carbon-based photoresponsive nanoparticles, the goals of high photoresponsive efficiency, excellent mechanical properties and stable crystal structure are achieved.

Benefits of technology

Efficient photothermal conversion efficiency (>80%) and excellent mechanical properties are achieved, ensuring structural integrity and photothermal activity of nanoparticles over an ultra-wide temperature range.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a high-entropy carbon-based photoresponsive nanoparticle and a preparation method and application thereof, wherein the high-entropy carbon-based photoresponsive nanoparticle is suitable for photoresponsiveness and light energy conversion in an ultra-wide temperature range (-196-1500°C), and the high-entropy carbon-based photoresponsive nanoparticle includes a single crystal carbide, and the high-entropy carbon-based photoresponsive nanoparticle matrix phase is a continuous solid solution including carbon, zirconium and a transition metal element group; the transition metal element group includes four or more of IV transition metal elements or V group transition metal elements. Compared with the prior art, the present invention is based on a narrow bandgap zirconium carbide material to form a zirconium carbide-based high-entropy ceramic, which has the advantages of high photoresponsiveness efficiency, excellent mechanical properties and stable crystal structure, and the preparation method of the single crystal high-entropy carbon-based photoresponsive nanoparticle is simple and low in cost, and has broad application prospects in the fields of energy, medicine and thermal management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy ceramics, and in particular to high entropy carbon-based light-responsive nanoparticles and a preparation method and application thereof. Background Art

[0002] In the construction of resource conservation and environmental protection, the absorption and utilization of green energy such as light energy has become a research focus and hotspot. Photoresponsive nanoparticles are a special material that can absorb sunlight and convert it into heat and other energy. They have broad application prospects in the fields of energy, medicine and thermal management. At present, the research on photoresponsive materials mainly includes precious metal-based, semiconductor-based, conjugated polymer-based and carbon-based. Among them, the sources of precious metal-based and semiconductor-based raw materials are limited and expensive; the conjugated polymer-based synthesis path is long and it is difficult to achieve large-scale production. Therefore, carbon-based photoresponsive materials have received widespread attention, but traditional photoresponsive carbon-based materials such as zirconium carbide have problems such as low photothermal conversion efficiency and unstable crystal structure.

[0003] In recent years, new materials with excellent performance have continuously emerged and have become research hotspots. High-entropy ceramics developed from high-entropy alloys are one of the typical representatives. High-entropy ceramics usually refer to solid solutions formed by five or more ceramic components. Due to their unique "high entropy effect" and superior performance, they have become a hot topic in the ceramic field in recent years.

[0004] However, at present, the research on high-entropy ceramics is still in its infancy, and a lot of work focuses on composition design, single-phase formation ability, preparation methods, basic properties, etc. There are still many problems to be solved. Therefore, there is an urgent need for a high-entropy carbon-based photoresponsive nanoparticle and its preparation method and application to solve the problems of low response efficiency and unstable crystal structure of traditional carbon-based photoresponsive materials. Summary of the invention

[0005] The purpose of the present invention is to provide a high-entropy carbon-based photoresponsive nanoparticle and a preparation method and application thereof in order to solve the above-mentioned problems. Based on narrow-bandgap zirconium carbide materials, zirconium carbide-based high-entropy ceramics are formed, which have the advantages of high photoresponsive efficiency, excellent mechanical properties and stable crystal structure. At the same time, in order to avoid many problems in traditional high-entropy ceramic solid-phase molding, such as uneven element mixing, element segregation, high impurity content and difficulty in forming single crystal carbides, a simple and low-cost preparation method of single crystal high-entropy carbon-based photoresponsive nanoparticles is developed specifically, which has broad application prospects in the fields of energy, medicine and thermal management.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a high-entropy carbon-based photoresponsive nanoparticle, which is suitable for photoresponse and light energy conversion in an ultra-wide temperature range (-196 to 1500°C). The high-entropy carbon-based photoresponsive nanoparticle includes single crystal carbide, and the matrix phase of the high-entropy carbon-based photoresponsive nanoparticle is a continuous solid solution including carbon, zirconium and a transition metal element group; the transition metal element group includes four or more of Group IV transition metal elements or Group V transition metal elements.

[0008] Furthermore, the molecular formula of the high entropy carbon-based photoresponsive nanoparticles is: a Zr b C c , wherein X is four or more of Ti, Hf, Nb, Ta, V, W (titanium, hafnium, niobium, tantalum, vanadium, tungsten), a is the sum of the stoichiometric numbers of all elements in X, and a=b, a+b=c.

[0009] Furthermore, the crystal structure of the high entropy carbon-based photoresponsive nanoparticles is a cubic system, and the space group is The particle size is 50-300nm, and the photothermal conversion efficiency is greater than 80%.

[0010] Furthermore, the hardness of the high-entropy carbon-based photoresponsive nanoparticles is as high as 15 to 50 GPa, and the elastic modulus is as high as 400 to 500 GPa.

[0011] A second object of the present invention is to provide a method for preparing the above-mentioned high entropy carbon-based light-responsive nanoparticles, the preparation method comprising the following steps:

[0012] 1) adding a zirconium source, an inorganic precursor of a transition metal element group (four or more inorganic precursors of group IV or V) and a chelating ligand into a compound solvent and uniformly mixing them to obtain a uniform sol;

[0013] 2) subjecting the uniform sol obtained in step 1) to high-humidity negative pressure suction under stirring to obtain a zirconium-based inorganic gel;

[0014] 3) subjecting the gel obtained in step 2) to a first high-energy ball milling to achieve atomic-level uniform distribution of inorganic elements to obtain a uniform gel;

[0015] 4) After the uniform gel obtained in step 3) is fully dried, it is graded calcined under a protective gas atmosphere, firstly slowly heating to 800° C. at a heating rate in the first stage and keeping the temperature for 2 hours to remove the organic side groups of the colloid, and then rapidly heating to 1500-2000° C. at a heating rate in the second stage that is greater than the heating rate in the first stage to achieve rapid carbonization, thereby obtaining a single crystal high entropy carbon-based powder;

[0016] 5) The single crystal high entropy carbon-based powder obtained in step 4) is subjected to a second high-energy ball milling to rapidly crush it into nano-scale particles, namely the high entropy carbon-based photoresponsive nanoparticles.

[0017] Furthermore, in step 1), the transition metal element group includes four of the group IV transition metal elements or the group V transition metal elements; the molar ratio of the zirconium source to the four group IV transition metal elements or the group V transition metal element inorganic precursors is 1:0.25:0.25:0.25:0.25; and the molar ratio of the zirconium source to the chelating ligand is 1:0.01 to 0.05.

[0018] Furthermore, the “amount of substance” of each Group IV transition metal element or Group V transition metal element in the transition metal element group is the same.

[0019] Furthermore, in step 1), the mixing process is to perform magnetic stirring at room temperature (20-30° C.) at a speed of 200-500 r / min for 4-10 hours.

[0020] Furthermore, the zirconium source may be one or more combinations of zirconium isopropoxide, zirconium n-propoxide, zirconium n-butoxide, zirconium isobutoxide, zirconium tetrapentoxide, zirconium acetylacetonate or zirconium acetate.

[0021] Furthermore, the chelating ligand may be one or more combinations of acetic acid, hydrochloric acid, oxalic acid, citric acid, ammonium citrate, aminotriacetic acid or ethylenediaminetetraacetic acid.

[0022] Furthermore, the compound solvent can be a mixed solvent of water and alcohol in a volume ratio of 1:4, and the alcohol can be one or more combinations of methanol, ethanol, isopropanol, n-propanol, n-butanol, tert-butanol, ethylene glycol or butanediol.

[0023] Furthermore, in step 2), the environmental humidity of the high-humidity negative pressure suction is 85-99%, the negative pressure is 0.5-5 MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.

[0024] Furthermore, in step 3), the first high-energy ball milling is zirconium ball dry milling, with a rotation speed of 200 to 500 rpm and a time of 0.5 to 3 hours.

[0025] Furthermore, in step 4), the drying process is 80° C., vacuum drying for 4 to 10 hours.

[0026] Furthermore, in step 4), the protective gas is high-purity nitrogen (purity not less than 99.99%), the heating rate of the front section is controlled at 2-5°C / min, the heating rate of the rear section is controlled at 10-20°C / min, and the insulation time is 5-30min.

[0027] Furthermore, in step 5), the second high-energy ball milling is zirconium ball dry milling, with a rotation speed of 300 to 500 rpm and a time of 3 to 8 hours.

[0028] The third object of the present invention is to provide an application of the above-mentioned high entropy carbon-based photoresponsive nanoparticles, and to use the high entropy carbon-based photoresponsive nanoparticles in the field of photoresponsive energy-saving material preparation.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. The high-entropy carbon-based photoresponsive nanoparticles of the present invention have small particle size (50-300nm), high purity, no element segregation, high hardness, single crystal, and stable crystal structure. At the same time, their light conversion efficiency is high (>75%), and they can be widely used in the field of light-responsive energy saving.

[0031] 2. The present invention is based on narrow-bandgap zirconium carbide materials to form zirconium carbide-based high-entropy ceramics, which have the advantages of high photoresponse efficiency, excellent mechanical properties and stable crystal structure. At the same time, in order to avoid many problems in traditional high-entropy ceramic solid-phase molding, such as uneven element mixing, element segregation, high impurity content and difficulty in forming single crystal carbides, a simple and low-cost method for preparing single crystal high-entropy carbon-based photoresponsive nanoparticles is developed specifically, which has broad application prospects in the fields of energy, medicine and thermal management. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0033] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.

[0034] In the following examples of the present invention, all raw materials are commercially available.

[0035] Example 1

[0036] This embodiment provides a method for preparing high entropy carbon-based photoresponsive nanoparticles, comprising the following steps:

[0037] In order to realize the preparation of single crystal narrow band gap high entropy carbon-based materials, the present invention selects transition metal sources with similar atomic structure, similar atomic radius and narrow band gap as raw materials. Acetic acid, zirconium isopropoxide, hafnium n-propoxide, tetrabutyl titanate, vanadium acetylacetonate, and tungsten chloride are added to a mixed solvent of water and ethanol (volume ratio is 1:4) according to a stoichiometric ratio of 0.02:1:0.25:0.25:0.25:0.25, and stirred at room temperature at a speed of 300r / min for 6 hours. A mixed wet cold gas of ethanol / water below room temperature (10°C) is introduced into the solution at a gas flow rate of 100 mL / min, and a water pump is used to perform negative pressure suction to promote the reaction, ensuring that the humidity of the reaction system is ~90% and the negative pressure is ~2 MPa. After reacting for 30 minutes, the obtained inorganic gel is transferred to a ball mill, and the mass ratio of the gel to the mass of the zirconium ball is controlled to be 1:100. The ball milling is performed at a speed of 500 r / min for 3 hours to allow each inorganic source to form an atomic-level mixture. The obtained uniform gel is fully dried in a vacuum oven (80°C, 3 hours) and graded calcined in a nitrogen gas atmosphere. The front stage calcination is heated to 800°C at a heating rate of 2°C / min to remove organic side groups, and the rear stage calcination is heated to 1600°C at a heating rate of 10°C / min for rapid carbonization. Finally, the collected carbonized product was transferred to a ball mill, the mass ratio of carbonized product to zirconium ball was controlled to be 1:200, and the speed was 500r / min for 6 hours to obtain high entropy carbon-based photoresponsive nanoparticles. 0.125 Hf 0.125 V 0.125 W 0.125 )Zr 0.5 C is a cubic single crystal with a particle size of 85nm. All components are evenly distributed without element segregation. Its photothermal conversion efficiency is 82%, its hardness is 35GPa, and its elastic modulus is 421GPa. It can ensure structural integrity and photothermal activity in an ultra-wide temperature range (-196~1500℃). Compared with traditional carbon-based photothermal particles, the lattice distortion effect of the high entropy structure makes the theoretical band gap of the material narrower and the photothermal conversion efficiency higher.

[0038] Example 2

[0039] In order to realize the preparation of single crystal narrow band gap high entropy carbon-based materials, the present invention selects transition metal sources with similar atomic structure, similar atomic radius and narrow band gap as raw materials. Hydrochloric acid, zirconium isopropoxide, thallium acetate, tetrabutyl titanate, vanadium acetylacetonate, and tungsten chloride are added to a mixed solvent of water and ethanol (volume ratio is 1:4) according to a stoichiometric ratio of 0.02:1:0.25:0.25:0.25:0.25, and stirred at room temperature at a speed of 450r / min for 4 hours. A mixed wet cold gas of ethanol / water below room temperature (10°C) is introduced into the solution at a gas flow rate of 80 mL / min, and a water pump is used to perform negative pressure suction to promote the reaction, ensuring that the humidity of the reaction system is ~90% and the negative pressure is ~2 MPa. After reacting for 30 minutes, the obtained inorganic gel is transferred to a ball mill, and the mass ratio of the gel to the mass of the zirconium ball is controlled to be 1:100. The ball milling is performed at a speed of 500 r / min for 4 hours to allow each inorganic source to form an atomic-level mixture. The obtained uniform gel is fully dried in a vacuum oven (80°C, 3 hours) and graded calcined in a nitrogen gas atmosphere. The front stage calcination is heated to 800°C at a heating rate of 2°C / min to remove organic side groups, and the rear stage calcination is heated to 1500°C at a heating rate of 12°C / min for rapid carbonization. Finally, the collected carbonized product was transferred to a ball mill, the mass ratio of carbonized product to zirconium ball was controlled to be 1:200, and the speed was 500r / min for 6 hours to obtain high entropy carbon-based photoresponsive nanoparticles. 0.125 Ta 0.125 V 0.125 W 0.125 )Zr 0.5 C is a cubic single crystal with a particle size of 120nm. All components are evenly distributed without element segregation. Its photothermal conversion efficiency is 81%, its hardness is 32GPa, and its elastic modulus is 409GPa. It can ensure structural integrity and photothermal activity in an ultra-wide temperature range (-196~1500℃). Compared with traditional carbon-based photothermal particles, the lattice distortion effect of the high entropy structure makes the theoretical band gap of the material narrower and the photothermal conversion efficiency higher.

[0040] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A high entropy carbon-based photoresponsive nanoparticle, characterized in that: The high entropy carbon-based photoresponsive nanoparticles are suitable for photoresponsiveness and light energy conversion at -196 to 1500° C. The high entropy carbon-based photoresponsive nanoparticles include single crystal carbides, and the matrix phase of the high entropy carbon-based photoresponsive nanoparticles is a continuous solid solution including carbon, zirconium and a transition metal element group; The molecular formula of the high entropy carbon-based photoresponsive nanoparticle is: a Zr b C c , wherein X is four or more of Ti, Hf, Nb, Ta, V, and W, a is the sum of the stoichiometric numbers of all elements in X, and a=b, a+b=c; The photothermal conversion efficiency of the high entropy carbon-based photoresponsive nanoparticles is greater than 80%.

2. The high entropy carbon-based photoresponsive nanoparticle according to claim 1, characterized in that: The crystal structure of the high entropy carbon-based photoresponsive nanoparticles is a cubic system, and the space group is , particle size is 50~300nm.

3. A method for preparing high entropy carbon-based photoresponsive nanoparticles as described in any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: 1) adding a zirconium source, an inorganic precursor of a transition metal element group and a chelating ligand into a compound solvent and uniformly mixing them to obtain a uniform sol; 2) subjecting the uniform sol obtained in step 1) to high-humidity negative pressure suction under stirring to obtain a zirconium-based inorganic gel; 3) subjecting the gel obtained in step 2) to a first high-energy ball milling to achieve atomic-level uniform distribution of inorganic elements and obtain a uniform gel; 4) After the uniform gel obtained in step 3) is fully dried, it is subjected to graded calcination under a protective gas atmosphere, firstly heating to 800° C. at a heating rate in the first stage and keeping the temperature for 2 hours, and then heating to 1500-2000° C. at a heating rate in the second stage which is greater than the heating rate in the first stage, to obtain a single crystal high entropy carbon-based powder; 5) subjecting the single crystal high entropy carbon-based powder obtained in step 4) to a second high energy ball milling to crush it into nano-scale particles, namely the high entropy carbon-based photoresponsive nanoparticles; In step 1), the transition metal element group is four of Ti, Hf, Nb, Ta, V, and W.

4. The method for preparing high entropy carbon-based photoresponsive nanoparticles according to claim 3, characterized in that: The molar ratio of the zirconium source to four transition inorganic precursors of Ti, Hf, Nb, Ta, V, and W is 1:0.25:0.25:0.25:0.25; The molar ratio of the zirconium source to the chelating ligand is 1:0.01-0.

05.

5. The method for preparing high entropy carbon-based photoresponsive nanoparticles according to claim 3, characterized in that: In step 2), the environmental humidity of the high-humidity negative pressure suction is 85-99%, the negative pressure is 0.5-5 MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.

6. The method for preparing high entropy carbon-based photoresponsive nanoparticles according to claim 3, characterized in that: In step 3), the first high-energy ball milling is zirconium ball dry milling, with a rotation speed of 200-500 rpm and a time of 0.5-3 hours.

7. The method for preparing high entropy carbon-based photoresponsive nanoparticles according to claim 3, characterized in that: In step 4), the protective gas is high-purity nitrogen, the heating rate of the front section is controlled at 2-5°C / min, the heating rate of the rear section is controlled at 10-20°C / min, and the insulation time is 5-30min.

8. The method for preparing high entropy carbon-based photoresponsive nanoparticles according to claim 3, characterized in that: In step 5), the second high-energy ball milling is zirconium ball dry milling, with a rotation speed of 300-500 rpm and a time of 3-8 hours.

9. Use of the high entropy carbon-based photoresponsive nanoparticles according to any one of claims 1 to 2 or the high entropy carbon-based photoresponsive nanoparticles prepared by the preparation method according to any one of claims 3 to 8, characterized in that: The high entropy carbon-based light-responsive nanoparticles are used in the field of preparing light-responsive energy-saving materials.

Citation Information

Patent Citations

  • High-entropy carbide ultrahigh temperature ceramic powder and preparation method thereof

    CN109180189A

  • Photo-thermal composite with light absorption and heating and heat storage functions and preparation method thereof

    CN109609100A